Salmonella Transiently Reside in Luminal Neutrophils in the Inflamed Gut - Loetscher, Yvonne; Wieser, Andreas; Lengefeld, Jette; Kaiser, Patrick; Schubert, Sören; Heikenwalder, Mathias; Hardt, Wolf-Dietrich; Stecher, Bärbel (PLOS ONE, 2012)
Background Enteric pathogens need to grow efficiently in the gut lumen in order to cause disease and ensure transmission. The interior of the gut forms a complex environment comprising the mucosal surface area and the inner gut lumen with epithelial cell debris and food particles. Recruitment of neutrophils to the intestinal lumen is a hallmark of non-typhoidal Salmonella enterica infections in humans. Here, we analyzed the interaction of gut luminal neutrophils with S. enterica serovar Typhimurium (S. Tm) in a mouse colitis model. Results Upon S. Tmwt infection, neutrophils transmigrate across the mucosa into the intestinal lumen. We detected a majority of pathogens associated with luminal neutrophils 20 hours after infection. Neutrophils are viable and actively engulf S. Tm, as demonstrated by live microscopy. Using S. Tm mutant strains defective in tissue invasion we show that pathogens are mostly taken up in the gut lumen at the epithelial barrier by luminal neutrophils. In these luminal neutrophils, S. Tm induces expression of genes typically required for its intracellular lifestyle such as siderophore production iroBCDE and the Salmonella pathogenicity island 2 encoded type three secretion system (TTSS-2). This shows that S. Tm at least transiently survives and responds to engulfment by gut luminal neutrophils. Gentamicin protection experiments suggest that the life-span of luminal neutrophils is limited and that S. Tm is subsequently released into the gut lumen. This “fast cycling” through the intracellular compartment of gut luminal neutrophils would explain the high fraction of TTSS-2 and iroBCDE expressing intra- and extracellular bacteria in the lumen of the infected gut. Conclusion In conclusion, live neutrophils recruited during acute S. Tm colitis engulf pathogens in the gut lumen and may thus actively engage in shaping the environment of pathogens and commensals in the inflamed gut.